2014
DOI: 10.1007/978-3-319-08795-5_18
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Clustering for Event Sequences and Its Impact on Next Process Step Prediction

Abstract: Abstract. Next step prediction is an important problem in process analytics and it can be used in process monitoring to preempt failure in business processes. We are using logfiles from a workflow system that record the sequential execution of business processes. Each process execution results in a timestamped event. The main issue of analysing such event sequences is that they can be very diverse. Models that can effectively handle diverse sequences without losing the sequential nature of the data are desired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…There are two types of partitional clusters: (1) sequential, and (2) simultaneous. Sequential clustering uses algorithm to separate the data points in particular order (Le et al , 2014). The order of the objects then influenced the cluster that they will be partitioned into.…”
Section: Interdependence Methodsmentioning
confidence: 99%
“…There are two types of partitional clusters: (1) sequential, and (2) simultaneous. Sequential clustering uses algorithm to separate the data points in particular order (Le et al , 2014). The order of the objects then influenced the cluster that they will be partitioned into.…”
Section: Interdependence Methodsmentioning
confidence: 99%
“…─ next event prediction [6,[11][12][13][14][15][16][17][18] ─ business process outcome prediction [19][20][21][22] ─ prediction of service level agreement violations [15,23] There are also various studies that handle various regression problems in the business process prediction domain:…”
Section: Predictive Business Process Managementmentioning
confidence: 99%
“…─ remaining time prediction [24][25][26][27] ─ prediction of activity delays [28] ─ risk prediction [29,30] ─ cost prediction [31] These studies use different machine learning approaches such as decision trees [21], support vector machines [16], Markov models [12], evolutionary algorithms [14] among others.…”
Section: Predictive Business Process Managementmentioning
confidence: 99%
“…The following studies address the next process event prediction that we investigate in this paper. A multi-stage model, which starts by clustering event sequences using the k-mean algorithm combined with sequential alignment, builds individual Markov models on the obtained clusters (Le et al 2014). Experiments were conducted on records of processes obtained from a telecommunication company.…”
Section: Related Workmentioning
confidence: 99%
“…An approach by Le et al (2017) uses sequential k-nearest neighbor classification and an extension of Markov models to predict the next process steps by considering temporal features. Using the same process log data as Le et al (2014), they showed the superiority of this model over Markov and Hidden Markov Models (HMM). Unuvar et al (2016) proposed a decision tree model to predict the next activity in running instances of processes with parallel execution paths.…”
Section: Related Workmentioning
confidence: 99%